School-based Simulated Internships to support dialogic collaboration and authentic links with the world of work: a design-based research study. Issue 1 (2nd January 2022) - Twiner, A.; Major, L.; Wegerif, R.
ABSTRACT: Employers often complain that students leave school unequipped with the real-world skills needed, including problem-solving, teamwork and effective communication. Conversely, school-based education often suffers from limited perceived authenticity leading to low student engagement. Work experience is one solution, but it is labour-intensive and inequitably available. To address these challenges we undertook design-based research to explore a new relationship between enterprise and education: potentially scalable, curricular-integrated, simulated role-play experiences of the world of work. We developed a programme aligned to the English Key Stage 3 Computing and Design and Technology curricula (students aged 11–14). Student groups designed, modelled or built local solutions to global challenges, presented via videos from engineers in two international telecommunications companies. 326 students participated, led by eight teachers in four schools in areas of England traditionally associated with low social mobility. Findings identify structures, resources and approaches that authentically link to the world of work, whilst supporting students' effective communication and shared group outcomes. We demonstrate proof of concept for an innovative education model made possible by the digital age. Using simulated real-world role-play scenarios, education across subjects could be made more authentic and many more students could experience working with leading-edge companies.